Disaster Risk Reduction Audits and BIM for Resilient Highway Infrastructure: A Proactive Assessment Framework - Seung-Jun Lee; Hong-Sik Yun; Ji-Sung Kim; Hwan-Dong Byun; Sang-Hoon Lee (Buildings)
Highway infrastructure faces growing exposure to natural hazards, necessitating more proactive and data-driven risk mitigation strategies. This study explores the integration of Disaster Risk Reduction Audits (DRRAs) into the lifecycle of highway infrastructure projects as a structured method for enhancing disaster resilience and operational safety. Using case analyses and scenario-based labor estimation models across design and construction phases, this research quantifies the resource requirements and effectiveness of DRRA application. The results show a statistically significant reduction in disaster occurrence rates in projects where a DRRA was implemented, despite slightly higher labor inputs. These findings highlight the value of adopting phased DRRA implementation as a national standard, with flexibility across different project types and scales. This study concludes that institutionalizing DRRAs, particularly when supported by digital platforms and decision-support tools, can serve as a critical component in transforming traditional infrastructure management into a more resilient and adaptive system.